Mediterranean countries and world food markets - Alexandratos N. (The GATT and Mediterranean agricultural trade, 1997)
The Mediterranean region as a whole might revert to being an ever-growing net cereals importer. Its capability to provision itself in world markets will depend on how other major importers and exporters will act. Future prospects in world cereals markets are briefly reviewed in the light of frequently expressed concerns that the balance between effective demand and supply may worsen. The policy reforms under the Uruguay Round may lead to world prices being a little above what they would have been without such reforms. Price variability may be no lower, and may actually be higher, because the policy reforms will lead to reduction in excess production in the main exporting countries, part of which was held by governments in stocks and acted as a buffer. The policy reforms of the UR are not expected to restrict significantly the scope for policies in support of agricultural development in the developing countries of the region. At the same time, such reform imply little progress towards improved access to import markets for their main agricultural exports, fruit and vegetables.
Séminaire sur 'Le GATT et les Echanges Agricoles Méditerranéens', 1995/12/03-05, Chania (Greece)